Medication Adherence of School Personnel in Public Secondary Schools of Tigaon District, Philippines - Joseph Bermido (Camarines Sur Polytechnic Colleges, 2024)
This study used the descriptive-correlational research method to determine the medication adherence of school personnel of select public schools in Tigaon, Camarines Sur. The respondents include 213 school personnel from public secondary schools of Tigaon, Camarines Sur. The data collected were classified and tabulated systematically and statistically treated using various statistical tools. The study concluded that most of the school personnel who participated in this study were 46 years old and above. The majority were female college graduates with a gross income of 22,000 to 44,000 pesos, assigned as classroom teachers, with no known illness or comorbidities, and had outpatient consultation more than 12 months ago; majority of the respondents were adherent to their medications; socio-economic factors, healthcare team and system-related factors, therapy-related factors, and patient-related factors are significant barriers to medication adherence; and there is significant relationship between medication adherence and sex, educational level, gross income per month, illness or comorbidities, and date of last outpatient consultation. Primary actions include strengthening health education that fosters a positive attitude towards medication adherence, additional resources for medicine supplies in schools and training for healthcare workers, improving the implementation of Gulayan sa Paaralan, and exploring options to simplify treatment regimens and affordable medications. With these, the researcher proposed measures and recommendations that school administrators and public school nurses can adopt to improve the health and safety of school personnel.